Study on the effectiveness of reading strategies in sustaining student’s interest in reading comprehension / Nelly Paya Soweng - Soweng, Nelly Paya (2007)
Reading is one of the four skills which students should have in order to perform well in their academic field. As such, reading comprehension is taught in schools to help students to master the reading skills which can come in handy when they leave school and enter the working world. However, there are still many students who do not have interest in reading comprehension lessons and many studies have been carried out to find out why this phenomenon occurs. Many theorists have come up with various suggestions which teachers could follow in order to sustain their students’ interest in reading. This study is undertaken to study the effectiveness ofreading strategies in sustaining students’ interest in reading comprehension and this involves 70 students from two classes from SMK Sungai Tapang, KM 13, Penrissen Road, 93250, Kuching. From this study, it is found that varying their strategies in their teaching; teachers can help to bring about a better performance in their students’ test. This is because the students are motivated and interested to learn and therefore participate whole-heartedly in the lessons.